Polypharmacy among patients with diabetes: a cross-sectional retrospective study in a tertiary hospital in Saudi Arabia. Issue 5 (24th May 2018) - Alwhaibi, Monira; Balkhi, Bander; Alhawassi, Tariq M; Alkofide, Hadeel; Alduhaim, Nouf; Alabdulali, Rawan; Drweesh, Hadeel; Sambamoorthi, Usha
Abstract : Abstract: Objectives: Patients with diabetes are at high risk for polypharmacy (ie, use of multiple medications) for treatment of diabetes, associated comorbidities and other coexisting conditions. This study aims to estimate the prevalence of polypharmacy and factors associated with polypharmacy among adult patients with diabetes. Methods: A cross-sectional retrospective observational study of adults with diabetes, who visited the outpatient clinic of a tertiary teaching hospital in Saudi Arabia, was conducted. Data were extracted from the Electronic Health Record database for a period of 12 months (January–December 2016). Polypharmacy was defined as the cumulative use of five or more medications. Polypharmacy among adults with diabetes was measured by calculating the average number of medications prescribed per patient. A multivariable logistic regression model was used to examine the factors associated with polypharmacy. Results: A total of 8932 adults with diabetes were included in this study. Of these, nearly 78% had polypharmacy which was more likely among women as compared with men and more likely among older adults (age ≥60 years) as compared with the adults. Also, polypharmacy was two times as likely among patients with coexisting cardiovascular conditions (adjusted OR (AOR)=2.89; 95% CI 2.54 to 3.29), respiratory disease (AOR=2.42; 95% CI 1.92 to 3.03) and mental health conditions (AOR=2.19; 95% CI 1.74 to 2.76), and three times as likely among patients with coexisting musculoskeletal disease (AOR=3.16; 95% CI 2.31 to 4.30) as compared with those without these coexisting chronic conditions categories. Conclusions: Polypharmacy is common among patients with diabetes, with an even higher rate in older adults patients. Healthcare providers can help in detecting polypharmacy and in providing recommendations for simplifying medication regimens and minimising medications to enhance the outcome of diabetes care.